Effect of job stress, emotional weakness and job satisfaction on intention to leave - Yo, Putu Melati Purbaningrat; Supartha, W. G. (International research journal of management, IT and social sciences, 2019)
This study used variable job stress, job satisfaction, job exhaustion and intention to leave. Aim to examine the effect of job stress variables on intention to leave, job satisfaction on intention to leave, emotional exhaustion on intention to leave. Strengthened on the basis of the theory of discrepancy theory, two-factor theory and continuance commitment. This study uses saturated sampling, which is a total sample of 48 employees operating at Matahari Department Store, Lipo Mall, Kuta Mall. The method of data collection uses interviewees and questionnaires with primary and secondary data sources. The results of the study using multiple linear regression analysis showed job stress has a positive effect on intention to leave, job satisfaction has a negative effect on intention to leave and emotional exhaustion has a positive effect on intention to leave.